Zhinao Capsule Improved Sleep and Memory Disorders in APP/PS1 Mice via cAMP/PKA/CREB Signaling Pathway Modulation - Xi H; Xie W; Yang Y; Li X; Zhai S; Fang S; Yang Y; Rao Z; Yang W; Li H (Drug Design, Development and Therapy, 2025)
Hu Xi,1,2 Wenting Xie,2 Yue Yang,2 Xiang Li,2 Shu Zhai,2 Shuzhen Fang,2 Yulong Yang,2 Zhihong Rao,2 Wenming Yang,2– 4 Hao Li1 1Wangjing Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 2Department of Neurology, the First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, People’s Republic of China; 3Key Laboratory of Xin’an Medicine, Ministry of Education, Hefei, People’s Republic of China; 4Center for Xin’an Medicine and Modernization of Traditional Chinese Medicine, Institute of Health and Medicine, Hefei Comprehensive National Science Center, Hefei, People’s Republic of ChinaCorrespondence: Wenming Yang, Email yangwm8810@126.com Hao Li, Email xyhplihao196@126.comObjective: To evaluate the efficacy and therapeutic mechanism of Zhinao Capsule (ZNC) in alleviating memory impairment and sleep disorders through an integrated approach involving network pharmacology, molecular docking, and experimental validation with molecular biological techniques.Materials and Methods: Fifty APP/PS1 mice were randomly divided into five groups: donepezil hydrochloride tablets group (administered with Donepezil hydrochloride tablets (0.65 mg/(kg·d)), ZNC low-, medium-, and, high-dose groups (0.234/0.468/0.936 g/(kg·d)), the model and normal groups treated with 0.9% saline at a dose of 10 mL/(kg·d). Gavage was performed once daily for 28 consecutive days after acclimatization, feeding, and grouping. Behavioral, Hematoxylin and Eosin (H&E), and Immunohistochemistry (IHC) analyses were used to verify the in vivo efficacy of ZNC in APP/PS1 mice. Network pharmacology and molecular docking were employed to predict the potential molecular mechanisms of ZNC in alleviating Alzheimer′s Disease (AD) and related sleep disorders. Enzyme-Linked Immunosorbent Assay (ELISA), Quantitative Real-Time Polymerase Chain Reaction (RT-qPCR), and Western Blot (WB) analyses were used to establish whether ZNC modulated relevant pathways to exert therapeutic effects against AD-related sleep disorders.Results: PiezoSleep monitoring, Morris Water Maze (MWM), H&E, and IHC tests revealed that ZNC could restore impaired learning memory and sleep structures, improve the cellular morphology of neurons in the hippocampal CA1 and CA3 regions, promote neurogenesis, and increase synaptic plasticity. That neuroinflammation and the Cyclic Adenosine Monophosphate (cAMP)/Protein Kinase A (PKA)/ cAMP Response Element Binding Protein (CREB) signaling pathway were ZNC’s key avenues in alleviating AD-related sleep disorders. On the other hand, the IHC, WB, ELISA, and RT-qPCR tests confirmed that ZNC significantly upregulated Brain-Derived Neurotrophic Factor (BDNF), cAMP, PKA mRNA, CREB mRNA, p-PKA, p-CREB, Synaptophysin (SYN), and Postsynaptic Density Protein 95 (PSD-95), significantly downregulated Amyloid Beta 1– 42 (Aβ 1-42) and inflammatory factors such as Glial Fibrillary Acidic Protein (GFAP), Interleukin-6 (IL6), IL-1β, and Tumor Necrosis Factor-α (TNF-α), and upregulated neurotransmitters such as 5-Hydroxyindole-3-Acetic Acid (5-HIAA), 5-Hydroxy Tryptamine (5-HT), and Gamma-Aminobutyric Acid (GABA)(p< 0.01, p< 0.05).Conclusion: The present results show that ZNC can improve sleep and memory disorders in APP/PS1 mice via modulating the cAMP/PKA/CREB signaling pathway, attenuating Aβ and neuroinflammation, and improving synaptic plasticity.Keywords: Zhinao Capsule, cAMP/PKA/CREB signaling pathway, Alzheimer’s disease, sleep disorders, APP/PS1 mice, neuroinflammation